2020
DOI: 10.1016/j.neucom.2019.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Data, depth, and design: Learning reliable models for skin lesion analysis

Abstract: Deep learning fostered a leap ahead in automated skin lesion analysis in the last two years. Those models, however, are expensive to train and difficult to parameterize. Objective: We investigate methodological issues for designing and evaluating deep learning models for skin lesion analysis. We explore ten choices faced by researchers: use of transfer learning, model architecture, train dataset, image resolution, type of data augmentation, input normalization, use of segmentation, duration of training, additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 37 publications
1
41
0
2
Order By: Relevance
“…The exception is specificity, which not only shows the expected anti-correlation with sensitivity, but also tends to correlate negatively with most other metrics. Those tendencies had been already observed by Valle et al [29] on the evaluation of two architectures.…”
Section: Resultssupporting
confidence: 69%
See 4 more Smart Citations
“…The exception is specificity, which not only shows the expected anti-correlation with sensitivity, but also tends to correlate negatively with most other metrics. Those tendencies had been already observed by Valle et al [29] on the evaluation of two architectures.…”
Section: Resultssupporting
confidence: 69%
“…Performing a double transfer (ImageNet → retinopathy → melanoma) did not improve the results, compared with transferring from ImageNet alone. Using an exhaustive factorial design with 7 factors (network architecture, training dataset, input resolution, training augmentation, training length, test augmentation, and transfer learning) over 5 test datasets, for a total of 1280 experiments, Valle et al [29] showed that the use of transfer learning is, by far, the most critical factor. In a factorial Analysis of Variance, it explains 14.7% of the absolute performance variation and 62.8% of the relative variation (excluding residuals and the choice of test dataset), with high significance (p-value < 0.001).…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations